Solvent induced crystallization of 1,2,3,4(6),5-penta-O-acetyl-6(4)-O-[(1S)-10-camphor sulfonyl]-myo-inositol diastereomers associated via weak trifurcated C-H center dot center dot center dot O interactions - Manoj, Kochunnoonny; Gonnade, Rajesh G.; Shashidhar, Mysore S.; Bhadbhade, Mohan M. (CrystEngComm, 2012)
The title compound produced three different types of solvent inclusion crystals having a conserved dimeric association via trifurcated C-H center dot center dot center dot O interactions between the diastereomers. These `dimeric' units are organized differently to produce three crystal types containing guest molecules. In type I and II, unit translated dimers created voids for guest inclusion, whereas in type III the guest sites were produced by helical association of dimers. Inclusion of dichloromethane gave two different types of crystals; however, we were unable to obtain unsolvated crystals of the title compound.